Framing the US-China Trade Negotiations from the Perspective of Al Arabiya and CNBC Arabiya Media: Robert Etnman's Approach and 5W+H - Kafia Azzahro; Halimi Zuhdy (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyze how Al Arabiya and CNBC Arabiya frame news reports on the United States-China trade negotiations using Robert Entman’s framing theory. The research focuses on news published in May and October 2025, with the study context referring to trade meetings held in Geneva, Switzerland. The population of the study comprises all news reports related to the US-China trade negotiations in both media outlets, while the sample consists of two main articles directly reporting on the Geneva negotiation rounds. The research instrument includes a structured news analysis guide based on the 5W+1H framework and Entman’s four framing elements: Define Problems, Diagnose Causes, Make Moral Judgement, and Treatment Recommendation. Data were analyzed using a descriptive qualitative technique to identify issue selection, issue salience, and meaning construction within each media outlet. The findings show that Al Arabiya frames the negotiations from a bilateral and nationalistic standpoint, emphasizing political positioning and national interests. In contrast, CNBC Arabiya highlights the global economic implications of the trade war, stressing disruptions to supply chains, global market instability, and the involvement of third parties such as Switzerland and the WTO. These differences demonstrate that media framing significantly shapes public perceptions of international economic issues by selectively emphasizing certain facts and perspectives.